Vaginocutaneous fistula and inguinal abcess presented 6 years after tension-free vaginal tape sling - İLBEY, YUSUF ÖZLEM; Sahin, Ali Feyzullah; Ilbey, YUSUF ÖZLEM; Sahin, Nur (My University, 2013)
Surgical treatment of female stress urinary incontinence (SUI) has become very popular after respectable success with minimal invasive surgeries. This is the first report of long term vaginocutaneous fistula (VCF) plus inguinal abcess after tension-free vaginal tape (TVT). A 67 year-old woman with vaginal discharge lasting more than 3 years complained with a painful swelling in the left inguinal area for the last three months. She had a medical history of TVT sling procedure for SUI six years ago. She had no history of pelvic surgery, cancer treatment or pelvic irradiation before or after TVT sling. No urethrovaginal or vesicovaginal fistula was found in physical examination and cystocopy. MRI showed a vaginocutenaous fistula and inguinal abcess. This case highlights the need for a high index of suspicion for VCF after TVT.